The Comparison of p16 Protein Expression between Single and Multiple Seborrheic Keratosis - Indri Widya Sari; Yulia Farida Yahya; Suroso Adi Nugroho; Erial Bahar; Ika Kartika (HM Publisher, 2022)
Background. Seborrheic keratosis (SK) is a benign epithelial tumor that attacks adults, the elderly, and an increasing number of age-related lesions. Various risk factors influence the pathogenesis of SK, including genetic predisposition and sun exposure. Recently, SK associated with a theory of keratinocytes aging. The aging prevents unlimited and uncontrolled growth of damaged cells, thereby preventing degeneration, but on the other hand, increases the resistance of the cells to apoptosis. From previous studies, the expression of p16 protein increased substantially with age, thus enabling it to be a biomarker of cellular aging at the molecular level. This study was aimed to determine p16 protein expression between single and multiple seborrheic keratoses, the relationship between p16 protein expression in single and multiple SK, and p16 protein expression in the elderly. Methods. Observational study with a cross-sectional design was used to determine the comparison of p16 protein expression between single and multiple seborrheic keratoses was conducted from December 1, 2021, to January 31, 2022. According to the inclusion criteria, study participants with a total of 42 people were selected through the consecutive sampling method. Physical examinations, dermoscopic and histopathologic were carried out until the results were obtained. Then the data were analyzed using the Fisher Test, Chi-Square, with a 95% confidence interval (p <0.05). Results. Most SK patients were found in the age range of 60-69 years (38%), male gender (54.8%), sun-related occasional 3-6 hour per day (50%), location of SK in sun-exposed areas (83.3%), the number of multiple lesions (69%), size 1-2 cm (57.1%), disease duration > 3 years (54.8%), and have no comorbid (69%), an acanthotic subtype of SK (40.5%). All single SK patients have a negative-weak expression of p16 protein (38.2%). Multiple SK patients have a moderate-strong expression of p16 protein (100%) and negative-weak expression of p16 protein (61.8%). Based on statistical analysis using Fisher Exact test has a statistically significant to p16 protein expression with number SK lesion (p-value 0,043). Conclusion. There is a significant correlation between p16 protein expression with single and multiple SK. The study has several limitations. The sample size was small. Other supporting examinations are needed in SK, including polymerase chain reaction (PCR).